Optimasi Rata-rata Produksi Jagung di Kabupaten Limapuluh Kota Menggunakan Pemrograman Kuadratik Metode Wolfe - Sari Fitri; Helma Helma (Journal of Mathematics UNP, 2023)
This research was an experimented research that purpose to form a mathematical model for optimizing average corn production in Fifty Cities District with the constraint that the harvested area should not be more than the planted area and solve the model with the Wolfe quadratic programming method. The model of mathematical in the research was a model by formed nonlinear using the method of least squares. Then use the Wolfe method to form a new linear objective function and constraints in the form of Karush Kuhn-Tucker conditions. The results showed that the optimal average corn production in Fifty Cities District was 49.00456 tons/Ha with an optimal corn harvest area of 656.256 Ha.